Unveiling 2,000 years of differentiation among Tungusic-speaking populations: a revised phylogeny of the paternal founder lineage C2a-M48-SK1061 - Yu, Hui-Xin; Ao, Cheligeer; Zhang, Xian-Peng; Liu, Kai-Jun; Wang, Yi-Bing; Meng, Song-Lin; Li, Hui; Wei, Lan-Hai; Man, Da (Frontiers in Genetics, 2023)
Previous studies demonstrated Y chromosome haplogroup C2a-M48-SK1061 is the only founding paternal lineage of all Tungusic-speaking populations. To infer the differentiation history of these populations, we studied more sequences and constructed downstream structure of haplogroup C2a-M48-SK1061 with better resolution. In this study, we generated 100 new sequences and co-analyzed 140 sequences of C2a-M48-SK1061 to reconstruct a highly revised phylogenetic tree with age estimates. We also performed the analysis of the geographical distribution and spatial autocorrelation of sub-branches. Dozens of new sub-branches were discovered, many sub-branches were nearly unique for Ewenki, Evens, Oroqen, Xibe, Manchu, Daur and Mongolian. The topology of these unique sub-branches is the key evidence for understanding the complex evolutionary relationship between different Tungusic-speaking populations. The revised phylogeny provided a clear pattern for the differentiation history of haplogroup C2a-M48-SK1061 in the past 2,000 years.This study showed that the divergence pattern of founder lineage is essential to understanding the differentiation history of populations.